2020
DOI: 10.3390/ma13184214
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of an Adaptive GFRP Wind Barrier Structure for Railway Bridges

Abstract: Wind barrier structures on railway bridges are installed to mitigate the wind effects on travelling trains; however, they cause additional wind loads and associated aerodynamic effects on the bridge. An innovative concept was developed for a wind barrier structure in this study that used a glass–fibre–reinforced polymer (GFRP) that may deform properly when subjected to a crosswind. Such deformation then allows for wind to pass, therefore reducing the wind loads transferred to the bridge. Wind tunnel experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…The WVB coupling vibration analysis has been investigated in various aspects, including the determination of proper bridge stiffness [72], the wind barrier performance evaluation and optimization [69,[73][74][75][76][77][78] and the safety assessment of train passing the pylons [79].…”
Section: Effect Of Crosswinds On Train-bridge Systemmentioning
confidence: 99%
“…The WVB coupling vibration analysis has been investigated in various aspects, including the determination of proper bridge stiffness [72], the wind barrier performance evaluation and optimization [69,[73][74][75][76][77][78] and the safety assessment of train passing the pylons [79].…”
Section: Effect Of Crosswinds On Train-bridge Systemmentioning
confidence: 99%
“…Shown in Figure 2c is a noise barrier without PV panels. It should be mentioned that, although noise/wind barriers are not subjected to vehicle loads, the barriers may deform at the effects of wind, and the mechanical strain of the barriers may be transferred to the integrated PV panels [44] therefore, the strain effects on the PV panels should be investigated before their applications. Some barriers may also extend to the top of roads and cover the whole top and side faces of roads, providing more space for PV application, for example, 4400 PV panels were installed on the rooftop of the Blackfriars Railway Bridge in London.…”
Section: Other Accessory Facilities and Buildingsmentioning
confidence: 99%
“…Therefore, glass fiber reinforced polymer (GFRP) profiles are selected as the substrates due to their superior mechanical performance [63], cost effectiveness, resistance to aggressive environmental conditions [64], and electric insulation [65]. GFRP profiles have been used in multiple civil engineering scenarios, including retaining walls of road slopes [66], bridges [67], wind barriers [44], floor systems [68], and reinforcement for pavement [69]. In terms of the type of PV cells, a-Si PV cells were selected for the integration since existing applications suggested that the c-Si PV cells may not sustain long-term vehicle loads while flexible a-Si PV cells may operate normally even after deformation [17].…”
Section: Conceptual Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the effects of in-plane compressive strain on a-Si PV cells, the cells were adhesively bonded by an epoxy adhesive to GFRP square hollow sections and subjected to compressive loads [99]. GFRP materials were used due to their superior mechanical properties [106,107] and electrical insulation. The critical compressive strain was found to be related to the adhesive thickness, as it was about 0.2% for 2.0 mm adhesive and 0.5% for 0.5 mm adhesive, as also shown in Table 6.…”
Section: Strain Effects On Thin-film Flexible Pv Cells and Their Structural Integrationsmentioning
confidence: 99%